Some differential superordination results using a generalized Sălăgean operator and Ruscheweyh operator - ANDREI, Loriana (Studia Universitatis Babeș-Bolyai Mathematica, 2015)
In the present paper we establish several differential superordinations regarding the operator DRm defined by using Ruscheweyh derivative Rmf (z) and the generalized Sălăgean operator... A number of interesting consequences of some of these superordination results are discussed. Relevant connections of some of the new results obtained in this paper with those in earlier works are also provided. Mathematics Subject Classification (2010): 30C45, 30A20, 34A40.